V.A. Shchegoleva’s Diary of 1915 - Drovaleva, Natalia A.; Simonova, Olga A. (A.M.Gorky Institute of World Literature of the Russian Academy of Sciences, 2025)
This publication includes the 1915 diary of Valentina Andreevna Shchegoleva (maiden name Boguslavskaya, 1878–1931), actress, poet and wife of Pushkin scholar P.E. Shchegolev. She was known primarily as a recipient of three poems by A.A. Blok. The text of the diary currently stored at the Manuscript Department of IWL RAS is being published in full for the first time. The introductory article recreates Shchegoleva’s biography and describes how she met her future husband in exile in Vologda, her work in theaters, participation in creative sessions and meetings with poets and writers, and also provides an outline of her post-war life. It is assisted by the actress’ letters, written during the last decade of her life,
to N.G. Chulkova, which are being published for the first time, as well as excerpts from Chulkova’s memoirs, stored in the Manuscript Department of the RSL. The pages of this diary hold various descriptions of Petersburg intelligentsia’s everyday life, which help fill in the blanks in our understanding of the literary process in 1915. It brings to light certain aspects of life, writing and publishing activity of the Silver Age writers (F.K. Sologub, A.A. Blok, G.I. Chulkov, A.N. Chebotarevskaya, P.E. Shchegolev, A.M. Gorky, V.V. Mayakovski, L.N. Andreev, the Merezhkovskis, etc.) and Petersburg thespians.
Codex manuscriptus, issue 3.